MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMA NEGERI 3 PRABUMULIH-KOTA PRABUMULIH - eko martanti; saodin; an an andari (UNISAN JURNAL, 2024)
Abstract. The research was conducted using a qualitative descriptive approach. Data collection techniques used interview, observation and documentation methods. The results of this research are 1) Leadership management of school principals in improving the quality of learning is carried out through: (a) Principal planning is carried out bottom up and policies are carried out top down by carrying out a SWOT analysis, (b) Organizing is carried out by dividing tasks through a decision letter and stated in in the organizational structure. (c) Implementation is carried out through increasing teacher competence and increasing students’ interests and talents. (d) Supervision is carried out through a school supervision program which is carried out regularly. 2) Supporting factors in improving the quality of learning are the high interest of prospective students who want to enter the Kartika Scholar IT Vocational School, Purworejo, human resources, most of whom are undergraduate graduates, the support of committees and parents as well as DU/DI cooperation for internships and PKL places. , The inhibiting factor is that not all teachers understand the 2013 curriculum. Keywords: leadership management, school principal, learning quality